(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Marbled crayfish / marmorkrebs, parthenogenetically reproducing decapod crustacean of pet aquarium origin conventionally has been recognized as an undesirable species since it a) is an invasive pest dangerous for aquatic ecosystem resources because of its hardiness, omnivorousness, fast growth, self-cloning abilities; b) has little commercial value for food industry. However, recently an idea has been introduced about marmorkrebs as a promising cheap protein source, which can help to fight world hunger. Accordingly, research performed at Liepaja University (Latvia) was focused on marbled crayfish farming system design issues. Research paper presented discusses marmorkrebs survival capacities in small-volume microcosm tanks (made from recycled material), under harsh abiotic conditions. Pilot research results obtained will be used to develop experimental project on low-input microcosmic indoor aquaculture for marmorkrebs.